Designing and Immunomodulating Multiresponsive Nanomaterial for Cancer Theranostics - Khan, Amreen; Dias, Faith; Neekhra, Suditi; Singh, Barkha; Srivastava, Rohit (Frontiers in Chemistry, 2021)
Cancer has been widely investigated yet limited in its manifestation. Cancer treatment holds innovative and futuristic strategies considering high disease heterogeneity. Chemotherapy, radiotherapy and surgery are the most explored pillars; however optimal therapeutic window and patient compliance recruit constraints. Recently evolved immunotherapy demonstrates a vital role of the host immune system to prevent metastasis recurrence, still undesirable clinical response and autoimmune adverse effects remain unresolved. Overcoming these challenges, tunable biomaterials could effectively control the co-delivery of anticancer drugs and immunomodulators. Current status demands a potentially new approach for minimally invasive, synergistic, and combinatorial nano-biomaterial assisted targeted immune-based treatment including therapeutics, diagnosis and imaging. This review discusses the latest findings of engineering biomaterial with immunomodulating properties and implementing novel developments in designing versatile nanosystems for cancer theranostics. We explore the functionalization of nanoparticle for delivering antitumor therapeutic and diagnostic agents promoting immune response. Through understanding the efficacy of delivery system, we have enlightened the applicability of nanomaterials as immunomodulatory nanomedicine further advancing to preclinical and clinical trials. Future and present ongoing improvements in engineering biomaterial could result in generating better insight to deal with cancer through easily accessible immunological interventions.